Assessing Medical Student’s Ability to Interpret Traumatic Injuries on Computed Tomography Before and After the Third Year Clerkships - Werth, Brady; Nguyen, Barbara; Ward, Jeanette; Reyes, Jared; Helmer, Stephen D.; Nold, Joseph; Brewer, Nicholas; Haan, James (Kansas Journal of Medicine, 2018)
Introduction. Exposure to radiologic images during clinical rotationsmay improve students’ skill levels. This study aimed to quantifythe improvement in radiographic interpretation of life-threateningtraumatic injuries gained during third year clinical clerkships (MS-3).Methods. We used a paired-sample prospective study design tocompare students’ accuracy in reading computed tomography (CT)images at the beginning of their third year clerkships (Phase I) andagain after completion of all of their third year clerkships (Phase II).Students were shown life-threatening injuries that included head,chest, abdomen, and pelvic injuries. Overall scores for Phase II werecompared with Phase I, as well as sub-scores for each anatomicalregion: head, chest, abdomen, and pelvis.Results. Only scores from students participating in both Phase Iand Phase II (N = 57) were used in the analysis. After completingtheir MS3 clerkship, students scored significantly better overall andin every anatomical region. Phase I and Phase II overall mean scoreswere 1.2 ± 1.1 vs. 4.6 ± 1.8 (p < 0.001). Students improved the mostwith respect to injuries of the head and chest and the area of leastimprovement was in interpreting CT scans of the abdomen. Althoughimprovements in reading radiographic images were noted after theclerkship year, students accurately diagnosed only 46% of life-threateningimages on CT scan in the trauma setting.Conclusions. These results indicated that enhanced education isneeded for medical students to interpret CT scans.Kans J Med 2018;11(4):91-94.